Effect of Composition on Optical and Thermoelectric Properties of Microstructured p-type (Bi2Te3)x(Sb2Te3)1 – x Alloys - K. Sharma; M. Lal; V.K. Gumber; A. Kumar; N. Chaudary; N. Goyal (Журнал нано- та електронної фізики)
Semiconducting (Bi2Te3)x(Sb2Te3)1 – x alloys are among the best thermoelectric materials available today near room temperature. This property is largely attributed to compositional variations, resulting in improved figure of merit. Considering this, present study aimed at characterizing the optical and thermoelectric properties of microstructured p-type (Bi2Te3)x(Sb2Te3)1 – x alloys for enhanced thermoelectric efficiency. High performance microstructured p-type (Bi2Te3)x(Sb2Te3)1 – x alloys were prepared by melting technique. The phase, optical band gap, microstructure, carrier type concentration and thermoelectric properties of the prepared alloys were systematically investigated by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, hot probe p-n type tester, four-probe method, κ-probe method and Seebeck coefficient measurement system. The electrical conductivity and Seebeck coefficient were measured in the temperature range 298-473 K to elucidate the Sb content effect on the thermoelectric properties of the p-type (Bi2Te3)x(Sb2Te3)1 – x alloys. The optical band gap decreased with increasing Sb content. Also, with the increase of Sb content, the electrical conductivity increased substantially, the thermal conductivity increased significantly and the Seebeck coefficient decreased marginally, which lead to a great improvement in the thermoelectric figure of merit. The maximum power factor of 3.2 × 10 – 3 Wm – 1K – 2 and figure of merit of 0.72 were obtained at 300 K for the composition of 15 %Bi2Te3-85 %Sb2Te3.